PENGARUH MEDIA SOSIAL, MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN CAT JOTUN PADA TOKO CAHAYA WARNA DI KECAMATAN JEUNIEB - Aulal Rizky; Adnan Adnan (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study examines the effect of social media, promotion, and price on purchase decisions for Jotun paint at Cahaya Warna Store in Jeunieb subdistrict. The data used in this study was primary data obtained by distributing questionnaires to 105 respondents. The data analysis method used was multiple linear regression analysis with the help of SPSS 26. The results partially showed that social media positively and significantly influence purchasing decisions for Jotun paint at the Cahaya Warna store in Jeunieb subdistrict, and price positively and significantly influenced purchase decisions for Jotun paint at Cahaya Warna store in Jeunieb subdistrict. Simultaneously, social media, brand, and price influenced purchasing decisions for Jotun paint at Cahaya Warna store in Jeunieb subdistrict.